Neuropsychiatric aspects of concussion: acute and chronic sequelae. (2nd February 2017) - Rao, Vani; Syeda, Arshiya; Roy, Durga; Peters, Matthew E; Vaishnavi, Sandeep
Concussion – also known as mild traumatic brain injury – is a transient disturbance of neurological function resulting from traumatic forces imparted to the brain that often produce cognitive, behavioral and systemic symptoms. In this review of the literature, we discuss the pathophysiology of both acute and chronic neuropsychiatric sequelae of concussions, followed by a brief overview of evaluation and management of these sequelae.